(3GdHQb GdjeGfi aj GdaJM GdYKeGfis - (3bWH GdOjf GdfgQhGfis ((3efUhQ Hf Sdje GdOefGhi GdCRgQi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg fUQ GdOjf GdMfjai HUGQe hSfGf s
(3BNQgG (B:s
(3hgPG BNQ eG CLQi Gddg Hg Gdbde hYdi Bdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs